Reception of chapter «Devil. Nightmare of Ivan Feodorovich» from a novel «Karamazovy Brothers» F. M. Dostoevsky in literature of Silver century - Калениченко, Ольга Николаевна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
In the article literature works of Silver century («Delusion» of M. Gor'kiy and «Rest» of L. Andreev) are examined, incoming in an original dialog which expressly exposes the features of the writers reception of chapter of «Devil. Nightmare of Ivan Feodorovich» from a novel «Karamazovy Brothers» F.M. Dostoevsky. An analysis rotined that the considered works leaned against the structure of chapter of novel «Karamazovy Brothers» of «Devil. Nightmare of Ivan Feodorovich» and opening in the image of devil by Dostoevsky. At the same time writers, exposing imperfect nature of modern man, reasons of its imperfection explain variously. Early Gor'kiy, depending upon reason, disbelieves in possibility of spiritual forces of man. L. Andreev unseals the tragedy of man life through the prism of expressionist and existential attitudes and, thus, does a step forward in understanding of ХХ century man nature. Except for it, it appears that «Rest» is tricked into by a result to the comprehension of Silver century literature of novel problems of F.M . Dostoevsky «Karamazovy Brothers» and in particular chapters of «Devil. Nightmare of Ivan Feodorovich».